In-vitro and in-vivo anti-inflammatory properties of extracts and isolates of Pangdahai - Oppong, M. B.; Lartey, M.; Adutwum, L. A.; et al (Phytomedicine Plus, 2024)
Background: : Pangdahai (matured, ripened, and dried seeds of Scaphium affine (Mast.) Pierre) is widely used in managing several diseases in countries like China, Vietnam, Japan, and India. This study evaluated the anti-inflammatory effects of the crude extracts (ethanol and aqueous) and isolated compounds of Pangdahai. Methods:: Xylene-induced ear edema in mice, carrageenan-induced paw edema in rats, and nitric oxide (NO) assay were used to evaluate and screen the crude extracts and isolated compounds from the ethanolic extracts of Pangdahai. TNF-α and IL-1β levels in the tissues of rat foot and ear were determined by ELISA. The cytotoxicity of the isolated compounds was also determined by MTT assay. Molecular docking studies using targets involved in the inflammatory process were also used to further evaluate the compounds. Results: : Both aqueous and ethanol extracts demonstrated significant anti-inflammatory effect and markedly attenuated vascular permeability in mice induced by acetic acid in a dose-independent manner. The ethanol extract also significantly inhibited levels of IL-1β and TNF-α. Four (4) compounds exhibited significant inhibitory effects on NO release without cytotoxicity on RAW 264.7 macrophage. These compounds also showed good binding affinities for COX-2, PLA2, IRAK-4 and NIK. Conclusions: This study validates, provides scientific evidence and justification for the use of the aqueous de coctions of Pangdahai in pharyngitis traditionally. (+) – Pinoresinol, tiliroside, Z-caffeic acid, and 3,4-dihydrox ybenzoic acid (protocatechuic acid) isolated from Pangdahai showed anti-inflammatory activities, which might be responsible for the actions of Pangdahai. Tiliroside showed a high binding affinity comparable to the native ligands of inflammatory mediators.
Research Article
Keywords: Pangdahai; Anti-inflammation; Cytotoxicity; Secondary metabolites